Visualisasi Gedung Kampus 1 Universitas Muhammadiyah Sidoarjo MenggunakanAugmented Reality Sebagai Media Informasi - Taurusta, Cindy; Asiddiq, Afnizar Maulana; Suprianto1, Suprianto; Setiawan, Hamzah (Indonesian Journal Publisher, 2024)
The making of this application is as a promotional medium to increase the number of new students and introduce the campus when PMB conducts campus tours. Visualization of augmented reality (AR) campus 1 buildings at Muhammadiyah University of Sidoarjo as an information medium that can combine real and virtual objects in 3D buildings in real time. This study uses the Marker Based Tracking Method to produce applications that can display building visuals in 3D and can scan markers by pointing the smartphone camera at brochures from various angles including: top, left and right sides and back.